USING CANVA-BASED LEARNING MEDIA TO ENHANCE STUDENTS' PRESENTATION SKILLS IN INDONESIAN SECONDARY SCHOOL CLASSROOMS - Irwan Supriadin; Ahmad Syagif Hannany Mustaufy (SENSEI RESEARCH CENTER, 2025)
Presentation skill is one of the important skills that must be mastered by the students, but many students are still not confident and their slides are not interesting. Canva is an application that can be used to make good presentation media easily. This study discusses the use of Canva-based learning media to enhance students' presentation skills. The study used a mixed-method design with an experimental class and a control class. The data were collected through a presentation test, observation, interview, and journal. The result shows that the experimental class is better than the control class and the students are more enthusiastic and more confident when they use Canva. So, Canva-based learning media can be used by the teachers to teach presentation.